Redesenhando a representa??o dos povos ind?genas no contexto do ensino de Hist?ria: a contribui??o das obras de Daniel Munduruku - Silva, Bruna J?ssica Cabral (2023)
This work aims to bring elements of the redesigning of History textbooks of the 3rd and 4th years of elementary school based on the speeches of two works by the indigenous author Daniel Munduruku: "Meu Av? Apolin?rio: Um dive no Rio da Minha Mem?ria" and "O Kara?ba : A History of Pre-Brazil" and how these works lead to reflections in the teaching of History. The problematic put in question is the way in which the image of these peoples is drawn in the History textbooks of the early years, specifically the 3rd and 4th years of elementary school. The History textbooks selected for this research are part of the collection ?Buriti Mais Hist?ria" by the Editora Moderna (PNLD 2019/2022), updated according to the new National Common Curricular Base (BNCC). It should be noted that these materials were produced almost a decade after Law 11.645/08 came into force and almost two decades after Law 10.639/03, which established the mandatory teaching of Afro-Brazilian and indigenous themes in schools, not summarizing the history of these peoples to coloniality , enslavement and stereotype, but as protagonist historical subjects. However, the history we study in textbooks is very much related to the idealization created by the winners about the defeated, as commonly occurs in the records. Stereotypical representations end up associating indigenous peoples with beings who initiated a certain ?culture? from Iberian contact, and are therefore not considered interesting to the point of having a history disassociated with these groups. Afterall, as much as teachers try to problematize what is in these materials, the processes of appropriation of written content and associated images only address specific moments in the history of Brazil. In this sense, authors like Daniel Munduruku are very important for breaking paradigms created by the traditionally told history, rescuing the image of the people who lived here for centuries before the European invasion. Therefore, the colonial imagery discourses contained in the mentioned textbooks are studied and, based on this, are carried out analyzes of the deconstruction of stereotypes through the two selected works by Munduruku, discussing a teaching of History combined with the indigenous literature capable of corresponding to the reality of different groups.